A PUFs-based hardware authentication BLAKE algorithm in 65 nm CMOS. Issue 6 (2nd June 2016) - Zhang, Yuejun; Wang, Pengjun; Zhang, Xuelong; Weng, Xinqian; Yu, Zhiyi
ABSTRACT: This paper presents a hardware authentication BLAKE algorithm based on physical unclonable functions (PUFs) in Taiwan Semiconductor Manufacturing Company low-power 65 nm CMOS. To support hardware authentication feature, PUFs have been organised in BLAKE algorithm as the salt value. The trials table method is used to improve the robust of PUFs, resulting in approximately 100% stability against supply voltage variations form 0.7 V to 1.6 V. By discussing the G-function of BLAKE algorithm, the hardware implementation is considered for acceleration, resulting in significant performance improvements. The die occupies 2.62 mm 2 and operates maximum frequency 1.0 GHz at 1.6 V. Measured results show that PUFs have great random characteristic and the authentication chip dissipates an average power of 91 mW under typical condition at 1.2 V and 780 MHz. In comparison with other works, the PUFs-based BLAKE algorithm has hardware authentication feature and improves throughput about 45%.